Chemisorption of sulfur (IV) oxide using the horizontal apparatus with bucket-like dispersers - Helesh, Andriy; Yavorskyi, Viktor; Yavorskyi, Ivan (Eastern-European Journal of Enterprise Technologies, 2016)
Due to the growing energy consumption and increasing share of fuels with high sulfur content in the global energy balance, there is a need for new, highly efficient methods and apparatus for recycling exhaust SO2-containing gases. It is found that SO2-low-concentrated gases are advisable to recycle by the liquid-oxidation method using NaOH as an intermediate absorbent and air oxygen as oxidant. Effective head apparatus – horizontal apparatus with bucket-like dispersers (HABD) is proposed for the cleaning process. To confirm the effectiveness of this apparatus in the processes of chemisorption and liquid phase oxidation of SO2, a pilot study on enlarged laboratory setup, the head apparatus of which was a scale model of HABD is carried out. The study is conducted in a wide range of concentrations of SO2 (0,4...34·g/Nm3) and pH of absorbing solutions (pH=3...13) using modern gas-analyzing devices. It is found that the irrigation density of 0.5 m3/Nm3 is technologically feasible. The cleaning process is appropriate to perform under counterflow motion of phases, which will allow combining chemisorption and oxidation in one HABD, provide high degrees of recovery (99.9...100 %) and liquid phase oxidation (80...99 %) of SO2. Due to the high velocity of dispersed droplets of ~ 10 m/s and intensive interphase renewal, it is managed to significantly reduce the diffusion resistance in the gas phase and transfer the process to the liquid film and provide high mass transfer coefficients of 0,82·10-4…1,80·10-4 (Pa·s·m3). It is found that at low initial concentrations of SO2 (0,4...7,74 g/Nm3), the process rate is limited by SO2 diffusion, and at high (10.54...33.89 g/Nm3) - NaOH diffusion. The process under study is described by the first-order reaction equation and is characterized by high values of the process rate constant – 0.46 s-1. Pilot studies confirm the high efficiency of HABD in the studied processes, prove the possibility of combining dust collection, chemisorption and oxidation stages in one apparatus.